Spatial and temporal variations of diffuse CO2 degassing at El Hierro volcanic system: Relation to the 2011–2012 submarine eruption. Issue 9 (18th September 2014) - Melián, Gladys; Hernández, Pedro A.; Padrón, Eleazar; Pérez, Nemesio M.; Barrancos, José; Padilla, Germán; Dionis, Samara; Rodríguez, Fátima; Calvo, David; Nolasco, Dacil
Abstract We report herein the results of extensive diffuse CO2 emission surveys performed on El Hierro Island in the period 1998–2012. More than 17, 000 measurements of the diffuse CO2 efflux were carried out, most of them during the volcanic unrest period that started in July 2011. Two significant precursory signals based on geochemical and geodetical studies suggest that a magma intrusion processes might have started before 2011 in El Hierro Island. During the preeruptive and eruptive periods, the time series of the diffuse CO2 emission released by the whole island experienced two significant increases. The first started almost 2 weeks before the onset of the submarine eruption, reflecting a clear geochemical anomaly in CO2 emission, most likely due to increasing release of deep‐seated magmatic gases to the surface. The second one, between 24 October and 27 November 2011, started before the most energetic seismic events of the volcanic‐seismic unrest. The data presented here demonstrate that combined continuous monitoring studies and discrete surveys of diffuse CO2 emission provide important information to optimize the early warning system in volcano monitoring programs and to monitor the evolution of an ongoing volcanic eruption, even though it is a submarine eruption.